2020
DOI: 10.1007/s00417-020-04942-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy-guided diode laser-assisted transcaruncular StopLoss Jones tube implantation for canalicular obstructions in primary surgery

Abstract: Purpose To introduce and evaluate a minimally-invasive endoscopy-guided transcaruncular laser-assisted StopLoss Jones tube (SLJT) implantation technique for severe canalicular obstructions in primary surgeries. Methods We retrospectively identified 12 adult patients (12 eyes) with severe epiphora secondary to long-segment canalicular obstructions. All the 12 eyes underwent an endoscopy-guided transcaruncular SLJT implantation with an 810-nm diode laser’s assistance as the primary surgical approach. Surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Also, in 1965 [22] it was reported that implantation of a Jones tube between the lacrimal lake of the medial canthus conjunctival sac and nasal cavity could be used to reconstruct the tear discharge passage in the treatment of severe obstruction of the superior and inferior canaliculi. Several studies [23][24][25] have reported improvements to the surgical procedure. However, The tube caused local irritation and discomfort to the patient [26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, in 1965 [22] it was reported that implantation of a Jones tube between the lacrimal lake of the medial canthus conjunctival sac and nasal cavity could be used to reconstruct the tear discharge passage in the treatment of severe obstruction of the superior and inferior canaliculi. Several studies [23][24][25] have reported improvements to the surgical procedure. However, The tube caused local irritation and discomfort to the patient [26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Ptosis surgery is now commonly carried out as a minimal incision levator advancement (MILA) or a posterior approach to Muller's muscle (MMR) and the levator to hide the wound completely. Dacryocystorhinostomies have been done endoscopically for some time, but in the last few years, transcanalicular laser-assisted lacrimal procedures have been studied and are already in use in some countries (84)(85)(86)(87).…”
Section: Ophthalmic Plastic and Reconstructive Surgerymentioning
confidence: 99%